2021
DOI: 10.3390/recycling6010006
|View full text |Cite
|
Sign up to set email alerts
|

Raising Awareness on Solid Waste Management through Formal Education for Sustainability: A Developing Countries Evidence Review

Abstract: Solid Waste Management (SWM) is a multifaceted problem comprising political, socioeconomic, institutional, and environmental aspects. Due to exponential urban growth, it has become one of the most significant issues faced by urban spaces in developing countries. The gap in environmental knowledge among the youth and the old within developing countries contribute to ecological issues or waste management problems, resulting in unsustainable development, with important consequences in low-income countries. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
105
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(191 citation statements)
references
References 118 publications
10
105
1
5
Order By: Relevance
“…To sustain solid waste management or environmental issues in developing countries, formal education for sustainable development is essential at all levels of education, able to trigger a whole societal transformation. For better environmental sustainability or waste management sustainability education, teachers with the right knowledge, attitude, skills, and innovation, are required (Debrah et al, 2021). Moreover, environmental knowledge is a term used to describe concepts and behavior patterns related to the environment.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To sustain solid waste management or environmental issues in developing countries, formal education for sustainable development is essential at all levels of education, able to trigger a whole societal transformation. For better environmental sustainability or waste management sustainability education, teachers with the right knowledge, attitude, skills, and innovation, are required (Debrah et al, 2021). Moreover, environmental knowledge is a term used to describe concepts and behavior patterns related to the environment.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Responses indicated that the guidelines presented by the school head were effectively clarified and well-discussed to the stakeholders of the school. The study of Debrah et al (2021) sought to establish that teachers' environmental knowledge influences how waste is practiced and managed in schools. Most teachers in developing countries lack practical environmental knowledge to impact positive environmental education in students, which will contribute to enhancing environmental sustainability.…”
Section: International Journal Of Research Studies In Education 61mentioning
confidence: 99%
See 1 more Smart Citation
“…Each year, human activities generate large amounts of wastes that have a negative impact on the environment and must be stored or treated [1]. Their minimization can be achieved by reusing and recycling, which will lead to the reduction of dependence on natural resources and the achievement of sustainable development objectives [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Due to an exponential growth in the use of cars in Kuwait, the accumulation of used tires poses a serious risk to the ecosystem; therefore, recycling waste products is vital [8][9][10]. Recently, great effort has been directed toward finding alternate ways to use waste materials emerging in the world [11][12][13].…”
Section: Introductionmentioning
confidence: 99%